COMPOSITE DEVELOPMENT STRATEGY IN THE NATUNA AREA COASTAL DEFENSE IN SUPPORTING THE MAIN TASKS OF THE INDONESIAN ARMED FORCE - Rachmat Triadi; Sutrisno Sutrisno; Okol Sri Suharyo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2022)
The Unitary State of the Republic of Indonesia is the largest archipelagic country in the world, where itsgeographical constellation which is in a cross-world position places the sea area of national jurisdiction verystrategically for both Indonesia and for other countries. The State Defense Policy of 2020 set by the Minister ofDefense of the Republic of Indonesia formulates that the implementation of National Defense is carried out in adirected, measurable, transparent and accountable manner, demanding the establishment of a Universal People'sSecurity Defense System (Sishankamrata) through efforts to manage national resources which include all humanresources, human resources and human resources. natural resources, artificial resources and nationalinfrastructure throughout the territory of the Republic of Indonesia as a defense unit in overcoming threats.Composite Company capabilities can still be developed by increasing the strength and capabilities of compositecompanies and optimizing the degree pattern. The Composite Company development strategy can be started byfirst studying the potential threats that may be in the future and analyzing the condition of the Composite Companywhich must be improved to create national maritime security. Based on these problems, this research offers astrategy for developing a composite company in maintaining national marine security that takes into accountpotential threats in the future. In this study, the authors analyzed the problem using the SWOT method. TheSWOT method is used to formulate the main strategy for the development of Composite Companies in the faceof national maritime security threats, and used to analyze the implementation of the Composite Company developmentstrategy in the face of national maritime security threats. The AHP method is used for decision-making involvinga number of criteria and alternatives selected based on consideration of all related criteria are used to determinethe priority scale of the strategy to be implemented for the advancement of the Navy.Keywords: Strategy, Composite Company, SWOT Method, Analytical Hierarchy Process (AHP) Method